Surface‐Embedded Stretchable Electrodes by Direct Printing and their Uses to Fabricate Ultrathin Vibration Sensors and Circuits for 3D Structures. Issue 43 (4th October 2017) - Song, Jun Hyuk; Kim, Young‐Tae; Cho, Sunghwan; Song, Woo‐Jin; Moon, Sungmin; Park, Chan‐Gyung; Park, Soojin; Myoung, Jae Min; Jeong, Unyong
Abstract: Printing is one of the easy and quick ways to make a stretchable wearable electronics. Conventional printing methods deposit conductive materials "on" or "inside" a rubber substrate. The conductors made by such printing methods cannot be used as device electrodes because of the large surface topology, poor stretchability, or weak adhesion between the substrate and the conducting material. Here, a method is presented by which conductive materials are printed in the way of being surface‐embedded in the rubber substrate; hence, the conductors can be widely used as device electrodes and circuits. The printing process involves a direct printing of a metal precursor solution in a block‐copolymer rubber substrate and chemical reduction of the precursor into metal nanoparticles. The electrical conductivity and sensitivity to the mechanical deformation can be controlled by adjusting the number of printing operations. The fabrication of highly sensitive vibration sensors is thus presented, which can detect weak pulses and sound waves. In addition, this work takes advantage of the viscoelasticity of the composite conductor to fabricate highly conductive stretchable circuits for complicated 3D structures. The printed electrodes are also used to fabricate a stretchable electrochemiluminescence display. Abstract : Stretchable electrodes surface‐embedded in rubber substrates are fabricated by a simple printing strategy. The process involves printing of a metal precursor and chemical reduction into metal nanoparticles. These printed electrodes are used as highly sensitive free‐standing thin‐film vibration sensors and highly stretchable electrical circuits for 3D structures.